2018
DOI: 10.1109/tbme.2017.2782781
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Non-Invasive 3-D Surveillance of Arteriovenous Fistulae Using Freehand Ultrasound

Abstract: Non-invasive 3-D surveillance of arteriovenous fistulae is possible, and a patient-specific geometry was created using ultrasound and optical tracking. Access to this non-invasive 3-D surveillance technique will enable future studies to determine patient-specific remodeling behavior, in terms of geometry and hemodynamics over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Access via an arteriovenous fistula requires either open surgery or an endovascular approach. While there is no literature for pre-procedure patient-specific 3D printed anatomic models, one study used 3D printing for arteriovenous fistula surveillance post-operatively [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Access via an arteriovenous fistula requires either open surgery or an endovascular approach. While there is no literature for pre-procedure patient-specific 3D printed anatomic models, one study used 3D printing for arteriovenous fistula surveillance post-operatively [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…A scanning and processing procedure was developed by our team specifically for geometric tracking and CFD modelling of AVFs, using a freehand ultrasound set-up combining B-mode scanning with 3D probe motion tracking as previously described (Carroll et al 2020;Colley et al 2018). A 3D tracking camera is mounted on the ultrasound, in line of sight with the patient as the scanner moves the tracked probe over the scan target location, sweeping along the vasculature to create a high-density stack of B-mode frames containing the lumen geometry.…”
Section: Scanning Systemmentioning
confidence: 99%
“…Pre-operatively, the cephalic vein had an average diameter size of 1 mm and more than 2 mm when a proximal venous tourniquet was applied. The 3D freehand ultrasound system (Colley et al 2018) was used to obtain the lumen geometry as shown in Fig. 2.…”
Section: Patient Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-specific AVF geometries are obtained using an unique and portable freehand ultrasound scanning system [8,14,5]. This geometry is imported into the ANSYS-ICEMv18.1 meshing tool and a polyhedral grid is constructed with twelve prism layers from the surface.…”
Section: Geometry and Meshmentioning
confidence: 99%